2006
DOI: 10.1038/sj.pcan.4500921
|View full text |Cite
|
Sign up to set email alerts
|

Prostate-specific symptoms of prostate cancer in a German general population

Abstract: Predominant symptoms in prostate cancer patients are erectile dysfunctions and urinary problems. As decreases of these functions can be attributed to disease and treatment but also to age-related decreases, we conducted a study on a German reference population measuring general quality of life (QoL) as well as prostate-specific symptoms. In cooperation with a German health insurance company, 3000 questionnaires were mailed to a randomly selected sample of men aged 45-75 years. Questionnaires used were the EORT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
8
0
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 9 publications
(12 reference statements)
6
8
0
4
Order By: Relevance
“…As with other survey based studies, the issue of how representative this sample of prostate cancer survivors are of the population is always some concern. However, the responses rates of ~40% in the current study were comparable to other studies in this area [13,34]. Further, as a cross-sectional comparison, it is not possible to determine causation, so that these differences in QOL may have been influenced by differences in these groups' perceptions of their QOL prior to the cancer diagnosis and/or treatment.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…As with other survey based studies, the issue of how representative this sample of prostate cancer survivors are of the population is always some concern. However, the responses rates of ~40% in the current study were comparable to other studies in this area [13,34]. Further, as a cross-sectional comparison, it is not possible to determine causation, so that these differences in QOL may have been influenced by differences in these groups' perceptions of their QOL prior to the cancer diagnosis and/or treatment.…”
Section: Discussionsupporting
confidence: 55%
“…The first is that the literature comprises studies that have compared prostate cancer survivors using ADT to prostate cancer survivors undergoing radiation therapy and radical prostatectomy [9] or active surveillance [9][10][11][12]. As ADT, radiation therapy and radical prostatectomy all have known side-effects and symptoms [7,13], a lack of many significant differences in the QOL of men using these therapies is of little surprise. Secondly, all of these studies were conducted in North America or Europe, with the North America studies involving data from 1994 and 1995 [9,10].…”
mentioning
confidence: 99%
“…Second, the study did not cover those who were withdrawn from AA treatment before 5 years. Furthermore, the response rates for NORM were only B35%, similar to other populationbased surveys addressing sexual function (1). Hence, possible selection bias with loss of representativity could be operating in both patients and NORM.…”
Section: Radiotherapy and Antiandrogens For Prostate Cancer A Berg Et Alsupporting
confidence: 55%
“…Concerning the influence of age on HRQOL, there are contradictory results in the literature relating to comparisons between younger and older patients [6,7] . However, there is a consensus to take age effects into consideration [8,9] .…”
Section: Introductionmentioning
confidence: 99%
“…There are only few studies that examine the QOL of cancer patients compared to the general population [8] . In addition, there are several other studies that found no differences in the global HRQOL between PCPs and agematched persons without cancer [10] .…”
Section: Introductionmentioning
confidence: 99%